AN IMPORTANT ELEMENTS IN PROMOTING READING COMPREHENSION - I Kadek Artayasa; Ni Komang Dwi Eka Yuliati (Yavana Bhasha : Journal of English Language Education, 2023)
Reading is a strong foundation that must be instilled in the early grades and is the key to successful learning in subsequent classes. The essence of reading is to understand what is being read. This study aims to analyze important elements in improving the teaching of reading for comprehension. This research is qualitative research with a descriptive approach. The stages passed in this research begin with planning, research, implementation, data analysis, and then writing reports. The subjects in the study were two supervisors, two literacy coaches, two principals and six early-grade teachers. The results of interviews and observations explain that there are nine important elements in improving the teaching of reading for understanding. Some of those things are getting into the habit of making connections between the book and the outside world.